Discovering your expressive body [videorecording] basic dance concepts in dance training utilizing Bartenieff fundamentals - Hackney, Peggy; Ramsey, Diane; Barteniff, Irmgard (Pennington, NJ Peggy Hackney and Diane Ramsey, 1981)
This comprehensive demonstration provides a basis for expanded knowledge knowledge of movement principles that lead to an articulate, more expressive body.
Total body Connectedness - Verticality - Lower Body Mobility - Upper Body Mobility - Diagonal Connections lower to upper - Movement with three Spatial Pulls - Weight Shift and Propulsion - Body Half-Action - Spiralling
Keywords: Dance -- Body Mobility